Orthopaedic surgery : principles of diagnosis and treatment - Wiesel, Brent B. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"The book is divided into two sections. The general principles portion presents orthopaedic basic science in sufficient detail to prepare the reader for the in-training and board examinations. It contains chapters on the basics of the various modalities commonly used for patient evaluation in orthopaedics and the evaluation and treatment of musculoskeletal infection, metabolic bone disease, and musculoskeletal oncology. In addition, an overview of rheumatologic diseases affecting the musculoskeletal system and the principles guiding the treatment of orthopaedic trauma and sports medicine patients are included. In the subspecialty section, each chapter addresses the functional anatomy, patient evaluation (history, physical examination, and imaging), traumatic injuries, and atraumatic conditions for a specific region of the body. For each diagnosis, the typical presentation, options for non-operative and operative management, and expected outcomes are discussed"--Provided by publisher.
(Publisher-supplied data) Chapter 1: Basic Science -- Chapter 2: Epidemiology and Biostatistics in Orthopaedic Surgery Keith D. Baldwin and G. Russell Huffman -- Chapter 3: Imaging in Orthopaedic Surgery Turner Vosseller and John N. Delahay[DM2] -- Chapter 4: Electrodiagnostic Testing Michael K. Kuo -- Chapter 5: Musculoskeletal Infections Andrew F. Kuntz, and John L. Esterhai -- Chapter 6: Metabolic Bone Diseases Aasis Unnanuntana, Brian P. Gladnick, Benjamin McArthur, Moira McCarthy, and Joseph M. Lane -- Chapter 7: Rheumatology and Immunology for the Non-rheumatologist Daniel J. Clauw and Jacob N. Ablin -- Chapter 8:Overview of Musculoskeletal Neoplasms Atul F. Kamath, Harish S. Hosalkar and Richard D. Lackman, MD -- Chapter 9: Principles of Sports Medicine F. Winston Gwathmey, Jr., Joseph M. Hart and Mark D. Miller -- Chapter 10: Principles of Orthopaedic Trauma Samir Mehta -- Chapter 11: Pediatric Orthopaedics -- Chapter 12: The Spine William Postma, Steven Scherping, William Lauerman, and Sam W. Wiesel -- Chapter 13: The Shoulder Brent B. Wiesel, Benjamin Shaffer and Gerald R. Williams -- Chapter 14: The Elbow Brian Magovern and Matthew L. Ramsey, MD -- Chapter 15: Hand and Wrist Nick Pappas, Jonas L. Matzon and Pedro K. Beredjiklian -- Chapter 16: The Hip and Femur Neil P. Sheth, J. Stuart Melvin, Charles L. Nelson and R. Bruce Heppenstall -- Chapter 17: Knee and Leg Injuries Todd Rimington, John Klimkiewicz and Freddie Fu -- Chapter 18: Knee Arthroplasty John A. Johansen, and Brian G. Evans -- Chapter 19: Foot and Ankle Benjamin D. Martin and Francis X. McGuigan.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Orthopedic surgery; Electronic books